Pathogenetic aspects of cardiovascular disorders in carbon monoxide poisoning and ways of their correction - Azimova S.B; Yuldoshev B.X (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Carbon monoxide (CO) poisoning leads to cardiovascular disorders due to reduced oxygen delivery and cellular dysfunction. CO binds to hemoglobin, forming carboxyhemoglobin, impairing oxygen transport and causing systemic hypoxia. This triggers oxidative stress, inflammation, and endothelial dysfunction, contributing to arrhythmias, hypotension, and myocardial injury. The primary treatment, including oxygen therapy and hyperbaric oxygen, helps reduce CO levels and improve oxygenation. Emerging therapies targeting oxidative stress and inflammation are being explored to prevent long-term cardiovascular complications. Early detection and appropriate treatment are crucial to improving outcomes in CO poisoning.